Mix and Use - Chaverri Peralta, Felipe (2016)
“Mix and Use” promotes the generation of commercial mixed-use with neighborhood character. The project is located in the adjacent north block of the Pacific Train Station and at the west of the Pacific neighborhood Park in the center of San José. The literal use of train cars appeals to the collective imaginary of the site and, following its longitudinal configuration, it begins to formulate a project based on the openings that are generated between full and empty wagons (only wagon structure).